Quantification of Plasma Cell-Free Circulating DNA at Different Stages of Colorectal Cancer. (26th November 2017) - Agah, Shahram; Akbari, Abolfazl; Talebi, Atefeh; Masoudi, Mohsen; Sarveazad, Arash; Mirzaei, Alireza; Nazmi, Farinaz
ABSTRACT: Cell-free circulating DNAs (cfcDNAs) have been recognized as promising biomarkers for a number of cancers. This study aimed to quantify the cfcDNA in colorectal cancer to assess its potential value as biomarker. Quantification of baseline cfcDNA was determined as the amount of free glyceraldehyde 3-phosphate dehydrogenase (GAPDH) in plasma, using quantitative real-time polymerase chain reaction (PCR). The calculated area under the curve (AUC) of receiver operating characteristic (ROC) for cfcDNA was 0.875 (95% CI, 0.811–0.94), which was indicative of a high discriminatory power ( p < 0.001) and significant accuracy in distinguishing cancer patients from healthy individuals. The quantification of cfcDNA could be useful for clinical settings of CRC.